A study on knowledge attitude and practices regarding HIV/AIDS among general population in a community of Kottarakkara, Kerala - John, Nimmy N.; Krishnan, Athira Krishnan; Doddayya, H. (International Journal Of Community Medicine And Public Health, 2021)
Background: HIV/AIDS epidemic has emerged as one of the most serious and enormous health problems associated with high morbidity and mortality rate. A prospective questionnaire based observational study was carried out in Kottathala community of Mylom Gramapanchayat, Kottarakkara to analyse the peoples knowledge on HIV/AIDS, as well as attitudes towards HIV patients and actual sex practices for the control or prevention of HIV. Methods: A total of 150 participants were interviewed by using a predesigned questionnaire and responses were reviewed and analysed by using descriptive statistics namely total numbers and percentage. Results: Out of 150 participants females were more (84%) and most of them were under the age group of 18-30 years. Majority of the participants had higher degree of education (51.33%) as they are still youth. The overall participants had a higher degree of knowledge regarding HIV and most of them had a positive attitude towards the HIV patients. Around 84% of participants had history of sexual intercourse but majority of them (46%) never used condoms during sexual intercourse in which, 11.33% only using condom regularly. Most of them were following unsafe sexual practices. Conclusions: This study concludes that the surveyed general populations had high knowledge and attitudes regarding HIV/AIDS and had risky sexual practices.